Pengaruh Tingkat Pengangguran, Pertumbuhan Penduduk dan Pertumbuhan Ekonomi Terhadap Indeks Pembangunan Manusia di Kota Banjarmasin - Apriliani, Nur Shella (PPJP ULM, 2024)
This research aims to see the variables of the Unemployment Rate, Population Growth and Economic Growth partially and simultaneously on the Human Development Index in Banjarmasin City as well as the factors that have the most dominant influence on the Human Development Index in Banjarmasin City. This research uses a multiple linear regression model with the Eviews 10 application. The results obtained from this research are that the Unemployment Rate, Population Growth and Economic Growth together have a significant effect on the Human Development Index in Banjarmasin City. This research explains 93% of the dependent variable while the other 7% is explained by other variables outside this research model. The Economic Growth variable is the variable that most dominantly influences the HDI in Banjarmasin City.